A sensitive electrochemical detection of metronidazole in synthetic serum and urine samples using low-cost screen-printed electrodes modified with reduced graphene oxide and C60 - Elsa Maria Materón; Ademar Wong; Tayane Aguiar Freitas; Ronaldo Censi Faria; Osvaldo N. Oliveira, Jr (Elsevier, 2021)
Monitoring the concentration of antibiotics in body fluids is essential to optimizing the therapy and minimizing the risk of bacteria resistance, which can be made with electrochemical sensors tailored with appropriate materials. In this paper, we report on sensors made with screen-printed electrodes (SPE) coated with fullerene (C60), reduced graphene oxide (rGO) and Nafion (NF) (C60-rGO-NF/SPE) to determine the antibiotic metronidazole (MTZ). Under optimized conditions, the C60-rGO-NF/SPE sensor exhibited a linear response in square wave voltammetry for MTZ concentrations from 2.5 × 10−7 to 34 × 10−6 mol/L, with a detection limit of 2.1 × 10−7 mol/L. This sensor was also capable of detecting MTZ in serum and urine, with recovery between 94% and 100%, which are similar to those of the standard chromatographic method (HPLC-UV). Because the C60-rGO-NF/SPE sensor is amenable to mass production and allows for MTZ determination with simple principles of detection, it fulfills the requirements of therapeutic drug monitoring programs.